Data structures and algorithms in c++ - Goodrich, Michael T.; Tamassia, Roberto; Mount, David M. (New Delhi: Wiley, 2004)
This book is designed to provide a comprehensive introduction to data structures and algorithms, including their design, analysis, and implementation. Each data structure is presented using ADTs and their respective implementations, and important design patterns are introduced as means to organize those implementations into classes, methods, and objects. It helps provide an understanding of the wide spectrum of skills ranging from sound algorithm and data structure design to clean and efficient implementation and coding of these designs in C++. The book contains many C++ code and pseudo-code fragments.
Bibliography 665-670p.; Index 671-683p.
Keywords: C++; Priority Queues; Data structures; Algorithms; Graphs